Inhibition of MAPK/ERK pathway promotes oligodendrocytes generation and recovery of demyelinating diseases. Issue 7 (28th February 2019) - Suo, Na; Guo, Yu‐e; He, Bingqing; Gu, Haifeng; Xie, Xin
Abstract: Oligodendrocytes (OLs) are the myelinating glia of the central nervous system. Injury to OLs causes myelin loss. In demyelinating diseases, such as multiple sclerosis, the remyelination is hindered principally due to a failure of the oligodendrocyte precursor cells (OPCs) to differentiate into mature OLs. To identify inducers of OPC to OL differentiation, a high‐throughput screening based on myelin basic protein expression using neural progenitor cells‐derived OPCs has been performed and, PD0325901—an MEK (MAPK kinase) inhibitor—is found to significantly enhance OPC to OL differentiation in a dose‐ and time‐dependent manner. Other MEK inhibitors also display similar effect, indicating blockade of MAPK–ERK signaling is sufficient to induce OPC differentiation into OLs. PD0325901 facilitates the formation of myelin sheaths in OPC–neuron co‐culture in vitro. And in experimental autoimmune encephalomyelitis model and cuprizone‐induced demyelination model, PD0325901 displays significant therapeutic effect by promoting myelin regeneration. Our results suggest that targeting the MAPK–ERK pathway might be an intriguing way to develop new therapies for demyelinating diseases. Main Points: MEK inhibitors, represented by PD0325901, promote oligodendrocyte generation. PD0325901 promotes myelin formation both in vitro and in vivo. The MAPK‐ERK pathway might be an intriguing target to develop new therapies for demyelinating diseases.